Novel epididymis-specific mRNAs downregulated by HE6/Gpr64 receptor gene disruption. - Davies, B; Behnen, M; Cappallo-Obermann, H; Spiess, A; Theuring, F; Kirchhoff, C (2007)
Targeted disruption of the epididymis-specific HE6/Gpr64 receptor gene in mice led to male infertility. In order to characterize the phenotype at a molecular level, we compared the gene expression patterns of wild type (wt) versus knockout (KO) caput epididymides. The caput region of KO males, although morphologically normal, nevertheless showed an aberrant expression pattern. Combining micro array analysis, differential library screening, Northern blot analysis and quantitative RT-PCR, we found that the knockout of the HE6/Gpr64 receptor was mainly associated with the downregulation of genes specific to the initial segment. The list of KO downregulated transcripts comprised Enpp2/autotaxin, the lipocalins 8 and 9, the beta-defensin Defb42, cystatins 8 and 12, as well as the membrane proteins Adam (A Disintegrin And Metalloprotease) 28, claudin-10, EAAC1, and the novel Me9. Clusterin/ApoJ and osteopontin/Spp1 mRNAs, on the other hand, were upregulated in the KO tissues. The Me9 transcript was studied in further detail, and we report here a cluster of related epididymis-specific genes. Me9 is specifically expressed in the initial segment and is representative of a novel and highly conserved mammalian gene family. The family consists of single-exon genes only; intron-containing paralogs have not yet been ascertained. The cloned cDNA sequences predicted hydrophobic polytopic membrane proteins containing the DUF716 motif. Protein expression was shown in the rodent caput epididymidis but remained uncertain in primates.